POTENCY OF LIGNOCELLULOSE DEGRADING BACTERIA ISOLATED FROM BUFFALO AND HORSE GASTROINTESTINAL TRACT AND ELEPHANT DUNG FOR FEED FIBER DEGRADATION - Wahyudi, A.; Cahyanto, M.N.; Soejono, M.; Bachruddin, Z. (Diponegoro University, 2010)
Lignin is limiting factor for cellulose and hemicellulose degradation in rumen. Isolation andselection bacteria from buffalo and horse gastrointestinal tract and elephant dung could be foundbacteria that have superiority to degrade lignin, xylan, and cellulose. Those animals were chosenbecause they were herbivores that consume low quality crude fiber as their main energy sources.Lignocellulose degrading bacteria were isolated by Hungate selective media, by using lignin (tannicacid), xylan, and cellulose as selective substrates. The morphological identification used an enrichmentmedia by measuring color, colony size, diffusion zone, clear zone, and biochemical identification usingproduction of ligninase, xylanase, and cellulase enzymes. The best lignocellulose degrading bacteriathen was determined by the morphological and biochemical character. This study showed thatlignocellulose degrading bacteria could be found in gastrointestinal tract of buffalo and horse, andelephant dung. Highest number colony was found in samples from buffalo's colon (376), followed byhorse's cecum (203), elephant’s dung (46), buffalo’s cecum (23), buffalo's rumen (9) and horse’s colon(7). The highest isolates activity of lignolytic, xylanolytic, and cellulolytic were reached by buffalo’scecum (7.64), horse's cecum (6.27), and buffalo’s colon (2.48). Meanwhile the highest enzymesproductivities were: buffalo’s cecum (0.0400 µmol), horse’s cecum (1.3912 µmol) and buffalo’s colon(0.1971 µmol). Based on morphologycal character and biochemical test, it could be concluded thatlignolytic from buffalo’s cecum, xylanolytic from horse’s cecum, and cellulolytic from buffalo’s colonwere the superior isolates and they were 99% analyzed as Enterococcus casseliflavus/gallinarumspecies.